Assessing progress in protecting non-smokers from secondhand smoke. Issue 6 (29th August 2018) - Semple, Sean; Mueller, Will; Leyland, Alastair H; Gray, Linsay; Cherrie, John W
Abstract : Objective: To examine trends in population exposure to secondhand smoke (SHS) and consider two exposure metrics as appropriate targets for tobacco control policy-makers. Design: Comparison of adult non-smokers' salivary cotinine data available from 11 Scottish Health Surveys between 1998 and 2016. Methods: The proportions of non-smoking adults who had measurable levels of cotinine in their saliva were calculated for the 11 time points. The geometric mean (GM) concentrations of cotinine levels were calculated using Tobit regression. Changes in both parameters were assessed for the whole period and also for the years since implementation of smoke-free legislation in Scotland in 2006. Results: Salivary cotinine expressed as a GM fell from 0.464 ng/mL (95% CI 0.444 to 0.486 ng/mL) in 1998 to 0.013 ng/mL (95% CI 0.009 to 0.020 ng/mL) in 2016: a reduction of 97.2%. The percentage of non-smoking adults who had no measurable cotinine in their saliva increased by nearly sixfold between 1998 (12.5%, 95% CI 11.5% to 13.6%) and 2016 (81.6%, 95% CI 78.6% to 84.6%). Reductions in population exposure to SHS have continued even after smoke-free legislation in 2006. Conclusions: Scotland has witnessed a dramatic reduction in SHS exposure in the past two decades, but there are still nearly one in five non-smoking adults who have measurable exposure to SHS on any given day. Tobacco control strategies globally should consider the use of both the proportion of non-smoking adults with undetectable salivary cotinine and the GM as targets to encourage policies that achieve a smoke-free future.